Randomized comparison of dry tablet insertion versus gel form of vaginal misoprostol for second trimester pregnancy termination - Pongsatha S. (2014)
Aim: To compare the effectiveness of vaginal misoprostol between dry tablet insertion and gel form for second trimester pregnancy termination. Methods: A non-blinded block randomized controlled trial was conducted on 148 pregnant women with live fetuses in the second trimester undergoing pregnancy termination. They were randomly allocated to receive vaginal misoprostol (400 μg) either dry tablet insertion (n = 72) or gel form (n = 76). The same dose was then repeated every 3 h if adequate uterine contraction was not achieved until 48 h after the initiation of misoprostol. If abortion did not occur within this period, the treatment was considered a failure and other technique of termination was then given based on the decision of the attending physicians and the cervical status. Results: The mean induction-abortion interval in group 1 (20.9 ± 12.3 h) was not significantly different from that in group 2 (17.7 ± 10.2 h). The mean total dose of misoprostol was also not significantly different between the two groups (group 1, 1556.9 μg; group 2, 1350.9 μg), but the adverse effects of misoprostol (chill and diarrhoea) were more common in the gel group. Conclusion: Tablet insertion or gel form of vaginal misoprostol have similar effectiveness but the gel form was associated with more common adverse effects. © 2008 The Authors.